Implementación de un prototipo alimentado con energía fotovoltaica para monitorear la calidad del agua en la Quebrada Grande usando IoT (2022)
Water quality directly affects all living beings that make use of it, and it is also of the utmost importance in any ecosystem. In the municipality of Santa Rosa De Viterbo (Boyacá) there is the Quebrada Grande water source, which supplies a large part of the population, making it a very important element for the development of the community. This water source has been threatened by various factors that can lead to its contamination.